Food sovereignty, food security and the contribution of agricultural law: XXX European Congress and Colloquium of Rural Law, Poznań, 18–21 September 2019 | XXXe Congrès et Colloque Européens de Droit Rural, Poznań, 18–21 septembre 2019 | XXX. Europäischer Agrarrechtskongress mit Kolloquium, Poznań, 18.–21. September 2019 - Norer, Roland (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
From 18 to 21 September 2019, the XXX. European Agricultural Law Congress of C.E.D.R took place in Poznań. The overarching theme of the Congress was "Food Sovereignty, Food Security and the Contribution of Agricultural Law". The scientific work was developed in three separate commissions. The colloquium was dedicated to the upcoming reform of the Common Agricultural Policy. This volume contains the general reports prepared by the three commissions during the congress and their conclusions, an account of the colloquium and a synthesis report.With contributions byDr. hab. Paweł A. Blajer | Prof. Dr. hab. Roman Budzinowski | Dr. Christian Busse | Prof. em. Margaret Rosso Grossman | Prof. Dr. hab. Aleksander Lichorowicz | Prof. Dr. Rudolf Mögele | Prof. Dr hab. Ryszard Naskręcki | Prof. Dr. Roland Norer | Dr. Ludivine Petetin | Jerzy Plewa | Ass.-Prof. Dr. Anikó Raisz | Prof. Dr. Jeroen Rheinfeld | Prof. em. Dr. Paul Richli | Ass.-Prof. Dr. Luigi Russo | Geoff Whittaker